Sticky market webs of connection – human and nonhuman market co-codification dynamics across social media. (4th April 2022) - Schöps, Jonathan David; Reinhardt, Christian; Hemetsberger, Andrea
Abstract : Purpose: Digital markets are increasingly constructed by an interplay between (non)human market actors, i.e. through algorithms, but, simultaneously, fragmented through platformization. This study aims to explore how interactional dynamics between (non)human market actors co-codify markets through expressive and networked content across social media platforms. Design/methodology/approach: This study applies digital methods as cross-platform analysis to analyze two data sets retrieved from YouTube and Instagram using the keywords "sustainable fashion" and #sustainablefashion, respectively. Findings: The study shows how interactional dynamics between (non)human market actors, co-codify markets across two social media platforms, i.e. YouTube and Instagram. The authors introduce the notion of sticky market webs of connection, illustrating how these dynamics foster cross-platform market codification through relations of exteriority. Research limitations/implications: Research implications highlight the necessity to account for all involved entities, including digital infrastructure in digital markets and the methodological potential of cross-platform analyses. Practical implications: Practical implications highlight considerations managers should take into account when designing market communication for digital markets composed of (non)human market actors. Social implications: Social implications highlight the possible effects of (non)human market co-codification on markets and consumer culture, and corresponding countermeasures. Originality/value: This study contributes to an increased understanding of digital market dynamics by illuminating interdependent market co-codification dynamics between (non)human market actors, and how these dynamics (de)territorialize digital market assemblages through relations of exteriority across platforms.